Package reliability modeling and design analysis of bio-sensors - Lim, Bee Huan. (2008)
Thirteen design variations will be analysed for the solder joint reliability. The Strain Energy Density will be obtained from the studies and the solder joint fatigue life predicted. The effects of the thickness and polyimide coating layer that protects the exposed die, will also be examined for package stress level.